ADH1B and ADH1C genotype, alcohol consumption and biomarkers of liver function: findings from a Mendelian randomization study in 58,313 European origin Danes. - Debbie A Lawlor; Marianne Benn; Luisa Zuccolo; N Maneka G De Silva; Anne Tybjaerg-Hansen; George Davey Smith; Børge G Nordestgaard (PLoS ONE)
Background The effect of alcohol consumption on liver function is difficult to determine because of reporting bias and potential residual confounding. Our aim was to determine this effect using genetic variants to proxy for the unbiased effect of alcohol. Methods We used variants in ADH1B and ADH1C genes as instrumental variables (IV) to estimate the causal effect of long-term alcohol consumption on alanine aminotransferase (ALT), γ-glutamyl-transferase (γ-GT), alkaline phosphatase (ALP), bilirubin and prothrombin action. Analyses were undertaken on 58,313 Danes (mean age 56). Results In both confounder adjusted multivariable and genetic-IV analyses greater alcohol consumption, amongst those who drank any alcohol, was associated with higher ALT [mean difference per doubling of alcohol consumption: 3.4% (95% CI: 3.1, 3.7) from multivariable analyses and 3.7% (-4.5, 11.9) from genetic-IV analyses] and γ-GT [8.2% (7.8, 8.5) and 6.8% (-2.8, 16.5)]. The point estimates from the two methods were very similar and statistically the results from the two methods were consistent with each other for effects with ALT and γ-GT (both pdiff>0.3). Results from the multivariable analyses suggested a weak inverse association of alcohol with ALP [-1.5% (-1 .7, -1.3)], which differed from the strong positive effect found in genetic-IV analyses [11.6% (6.8, 16.4)] (p diff<0.0001). In both multivariable and genetic-IV analyses associations with bilirubin and protrombin action were weak and close to the null. Conclusions Our results suggest that greater consumption of alcohol is related to poorer liver function as indicated by higher ALT, γ-GT and ALP, but not to clotting or bilirubin.